COMPARATIVE LEGAL ANALYSIS OF THE CONCEPT OF «PROPERTY» UNDER THE LEGISLATION OF UKRAINE AND ACCORDING TO THE PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Мачуська, Ірина; Гуляр, Тетяна; Чирик, Олена (SWorldJournal, 2025)
The article examines the concept of "property" in accordance with the practice of the European Court of Human Rights and in accordance with the legislation of Ukraine. It is noted that for public law the concept of "property" is one of the fundamental cat